Hotel and lodging management : an introduction - Stutts, Alan T.; Wortman, James (Hoboken, New Jersey : John Wiley & Son, Inc., 2006)
The operation of hotels, motels, and other lodging facilities presents unique problems for managers. Hotel and Lodging Management, Second Edition addresses the entire operation of a lodging facility, with an emphasis on the interrelationship between its departments.
Preface. Introduction. Chapter 1: Growth and Development of the Lodging Industry.-- Chapter 2: Organizational Structure.-- Chapter 3: The Front Office.-- Chapter 4: Housekeeping.-- Chapter 5: The Marketing and Sales Department-- Chapter 6: Human Resource Management. --Chapter 7: Hotel Food and Beverage.-- Chapter 8: Loss Prevention and Security-- Chapter 9: The General Manager.-- Chapter 10: Yield Management--. Chapter 11: Management Contracts and Franchise Agreements.-- Chapter 12: Time-Share and Vacation Ownership.-- Chapter 13: Resorts, Themed Lodging, and Special Lodging Environments.
Includes index.
Keywords: HOSPITALITY INDUSTRY -- MANAGEMENT